2015
DOI: 10.1177/1756285615610471
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between plasmapheresis and intravenous immunoglobulin in children with Guillain–Barré syndrome in Upper Egypt

Abstract: Objective: The aim of our study is to assess the clinico-electrophysiological profile of children with Guillain-Barré syndrome (GBS) in Upper Egypt and to compare the efficacy of plasmapheresis versus other treatment modalities. Patients and methods:This was a retrospective study of children from January 2010 to October 2014 diagnosed as GBS. It included 62 cases. Results: Acute inflammatory demyelinating polyradiculoneuropathy (AIDP) was the most prevalent type of GBS in our locality. As regards the treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
29
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 25 publications
6
29
3
2
Order By: Relevance
“…A case series by Vikrant et al involving 120 TPE sessions performed among 31 GBS patients reported 1 death, for a mortality risk of 3.2% . Saad et al retrospectively evaluated 62 children with GBS from Upper Egypt, comparing treatment outcomes of 32 patients who underwent TPE with those of 30 patients who received IVIG . Unlike our study, theirs suggested no difference in mortality risks between the two treatment modalities, although those who received IVIG had prolonged hospitalization, were less likely to recover, and more likely to require mechanical ventilation than those who underwent TPE …”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…A case series by Vikrant et al involving 120 TPE sessions performed among 31 GBS patients reported 1 death, for a mortality risk of 3.2% . Saad et al retrospectively evaluated 62 children with GBS from Upper Egypt, comparing treatment outcomes of 32 patients who underwent TPE with those of 30 patients who received IVIG . Unlike our study, theirs suggested no difference in mortality risks between the two treatment modalities, although those who received IVIG had prolonged hospitalization, were less likely to recover, and more likely to require mechanical ventilation than those who underwent TPE …”
Section: Discussioncontrasting
confidence: 56%
“…Previous studies primarily described outcomes of one of these two treatments using case series of patients diagnosed with GBS and/or similar conditions from a single institution. These studies often originated from developing countries . For instance, a retrospective study involving 230 South Indian TPE‐treated patients diagnosed with neurological disorders reported that GBS was a key diagnosis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,25 İmmünomodulatuvar tedaviler dışında destek tedavilerinin halen önemini koruduğu da unutulmamalıdır. Çocuk yaş grubunda PD deneyimli merkezlerde düşük komplikasyon oranlarıyla uygulanabilir ancak girişimsel işlemler gerektirmesi (santral kateter) ve özellikle küçük çocuklarda kan prime işlemine (setin işlem öncesi eritrosit süspansiyonu ile doldurulması) gereksinim duyulabilmesi dezavantajları arasındadır.…”
Section: Sonuçunclassified
“…[2] According to a study by Saad et al ., plasmapheresis (over IVIg) led to a significant reduction in the duration of hospitalization and faster recovery. [3] Further research is needed in milder disease and delayed treatment (>2 weeks after onset). IVIg is preferred than plasma exchange in children, due to ease of administration and avoidance of invasive catheters.…”
mentioning
confidence: 99%